Inequality among Mexican retail establishments in the context of COVID-19 - Cantero Ramírez, Margarita (2023)
Retail trade represents an important source of employment and its establishments are preferred spaces for the supply of Mexican families. However, the sanitary measures implemented have led to working conditions that show differences among them, and for this reason the objective of this study was to analyze how inequality in working conditions in traditional and modern retail trade occurs, through a qualitative study based on a narrative review of the literature. Among the results, the actions implemented by traditional and modern retailers to cope with the temporary closure of their commercial establishments, as well as disparities in their operation, stand out. The conclusion is the need to continue reflecting on commercial, labor and social practices influenced by the capital-labor relationship that go beyond individual and family control.